PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN IPS BERBASIS ASESMEN KOMPETENSI MINIMUM UNTUK MENINGKATKAN MUTU PEMBELAJARAN SISWA KELAS 8 SEKOLAH MENENGAH PERTAMA (SMP) - Solichul Achmada; Ngasbun Egar; Ghufron Abdullah (STKIP Subang, 2023)
Ideal learning in the classroom (interactive, interesting and memorable) certainly requires the support of learning devices and media to achieve quality learning. In the context of improving the quality of social studies learning, the teacher's role is very important in managing teaching and learning, starting from planning, implementation and evaluation/assessment. Quality learning is of course inseparable from the output (evaluation/assessment results) and is also related to the expected outcome (quality of graduates). In all this process, the development of learning tools and media in the form of Learning Videos is very necessary so that they are always dynamic and updated according to students' needs in the learning process. Based on surveys and initial research, it was found that so far the development and use of Learning Videos is still very minimal. As a result, teaching and learning in class tends to be monotonous, lacks variety in literacy and can trigger boredom among students in teaching and learning. We certainly don't want this together because it can lead to low student interest and enthusiasm in learning. For this reason, the author carried out research activities in the form of research and development of social studies learning videos as an effort to improve the quality of student learning in the classroom. This is expected to be able to comprehensively improve the quality of learning and the continuity of the process Social Sciences (IPS) subjects are compulsory subjects formed from the results of the multidisciplinary integration of social sciences and humanities which aims to provide experience and competence to students in overcoming problems or social problems in the surrounding community. In social studies learning, there are components that are interrelated and complement each other to achieve the desired goals, one learning component that must be held is learning media. social studies learning can run effectively learning media is needed, one of which is the use of video-based learning media. Using video-based media will help and facilitate teaching and learning activities. The objectives of this study were (1) to explain the process of developing video-based social studies learning media to improve the learning outcomes of eighth grade junior high school student eighth grade students of SMP ?, (2) Explain the effectiveness of video-based social studies learning media to improve the learning outcomes of seventh grade students of SMP Negeri 1 Pakis Aji dan SMP Negeri 2 Pakis Aji Kab. Jepara? The type of research used is research and development (Research and Development). The resulting product is a video-based learning media on social studies subjects for class eighth SMP student. The development model used is the Borg and Gall development model, with data collection techniques used are questionnaires, documentation, and learning outcomes tests. The results of this study are (1) The process of developing learning media uses ten steps, namely gathering initial information, planning, developing the initial product format, initial testing, product revision, field testing, product revision, field testing, final product revision, dissemination and implementation. (2) The effectiveness of the use of instructional media is described from the results of manual t-test calculations, namely results thitung and ttabel 21.92 ≥ 2.074, it can be concluded that H0 is rejected and H1 is accepted, so that there is a significant difference between the results of class learning using video-based social studies learning media and who do not use video-based social studies learning media